227k views
5 votes
Simplify the expression (2 square root sign 27) - (3 square root sign 32)

User Xeos
by
4.9k points

1 Answer

2 votes

Answer:

6
√(3) - 12
√(2)

Explanation:

Using the rule of radicals


√(a) ×
√(b)
√(ab)

Simplifying the radicals


√(27) =
√(9(3)) =
√(9) ×
√(3) = 3
√(3)


√(32) =
√(16(2)) =
√(16) ×
√(2) = 4
√(2)

Hence

(2 × 3
√(3)) - (3 × 4
√(2))

= 6
√(3) - 12
√(2)


User AliSh
by
5.2k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.